Are metabolic syndrome antecedents in prepubertal children associated with being born idiopathic large for gestational age?. Issue 8 (30th April 2013) - Çetin, Ceren; Uçar, Ahmet; Bas, Firdevs; Poyrazoğlu, Şükran; Bundak, Rüveyde; Saka, Nurçin; Özden, Tülin; Darendeliler, Feyza
<x xml:space="preserve">Abstract</x> Introduction Being born large for gestational age (LGA) is a risk factor for development of metabolic syndrome (MS) in adolescents and adults. Objective To evaluate prepubertal children born idiopathic LGA to non‐obese mothers without gestational diabetes or glucosuria with respect to the presence of MS antecedents. Patients and methods We conducted a cross‐sectional study to compare 40 (19 F) LGA‐born prepubertal children of a mean age of 6.1 ± 2.5 yr and 49 (25 F) appropriate for gestational age (AGA)‐born body mass index (BMI)‐matched peers of a mean age of 5.4 ± 1.8 yr with respect to their anthropometric data, blood pressure measurements, fasting serum glucose and insulin levels, homeostasis model assessment‐insulin resistance (HOMA‐IR), and lipids and atherogenic index (AI) [triglyceride (TG)/high‐density lipoprotein cholesterol (HDL‐C)]. HOMA‐IR > 2.5 was used to define IR. HDL‐C ≤ 40 mg/dL and TG ≥ 110 mg/dL were used to define dyslipidemia. Both groups were further divided into subgroups as obese and non‐obese according to their BMI percentiles and the analyses were repeated. Results Non‐obese LGA children had higher waist circumference (WC) standard deviation scores (SDSs) than BMI‐matched AGA‐born peers (p = 0.024). There were no significant differences between pooled, obese and non‐obese subgroups of LGA‐born children and their AGA counterparts with respect to dyslipidemia and IR. AI was higher in non‐obese LGA children than in AGA counterparts (p = 0.028). Conclusions Non‐obese idiopathic LGA‐born children have higher AIs than AGA‐born counterparts in the absence of IR. WC seems to be a good clinical screening tool in identifying at risk of non‐obese LGA children. Further studies are needed to evaluate MS antecedents in idiopathic LGA‐born children.